2017
DOI: 10.1111/1911-3846.12308
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Attribution and Information Transfers

Abstract: Managers frequently attribute the news in their earnings forecasts to various economic events. Using textual analysis, we identify the economic factors underlying earnings news from press releases. We document a wide range of industry-wide shocks and firm-specific actions to which the earnings news in management forecasts is attributed. As expected, earnings attributions significantly affect peer firms' price reactions to the earnings news. Specifically, earnings news attributed to industry-wide trends or firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
(89 reference statements)
1
17
0
Order By: Relevance
“…We argue that customers demand information about the supplier's future profitability and product market, including the information contained in management earnings and sales forecasts, because this information is an important aspect of firm viability. Moreover, prior studies have shown that management forecasts are usually accompanied with other related financial and nonfinancial information that explain or justify the forecasts (Baginski et al ; Hutton et al ; Koo et al ). These studies show that managers often supplement their firms' forecasts with explanations of relevant economic factors, such as changes in operational strategies, changes in product mix, and changes in product markets .…”
Section: Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
“…We argue that customers demand information about the supplier's future profitability and product market, including the information contained in management earnings and sales forecasts, because this information is an important aspect of firm viability. Moreover, prior studies have shown that management forecasts are usually accompanied with other related financial and nonfinancial information that explain or justify the forecasts (Baginski et al ; Hutton et al ; Koo et al ). These studies show that managers often supplement their firms' forecasts with explanations of relevant economic factors, such as changes in operational strategies, changes in product mix, and changes in product markets .…”
Section: Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
“…Several papers examine causal language and attributions using CL methods (Dikolli, Keusch, Mayew, & Steffen, ; Koo, Wu, & Yeung, ; Zhang & Aerts, ; Zhang, Aerts, and Pan, ). While these studies provide useful insights on aspects of causal reasoning, they focus primarily on measuring the incidence and volume of causal language using causation keywords rather than on distinguishing between defensive and enhancing attributions or identifying the nature of specific causal factor(s).…”
mentioning
confidence: 99%
“…Several papers have empirically examined information transfer in capital markets. For example, some papers focus on the information transfers from earnings announcements and conference calls (e.g., Brochet et al, 2018;Foster, 1981;Ramnath, 2002), while others focus on the transfers from management earnings forecasts (e.g., Baginski, 1987;Han et al, 1989;Kim et al, 2008;Koo, Wu, & Yeung, 2017;Pyo & Lustgarten, 1990) 7 The initial sample also includes transcripts from 2004, 2005, and 2006 but the coverage in these years is limited. So, transcripts from these years get dropped in latter analyzes.…”
Section: 1b the Self-improvement Motive And Upward Comparisonsmentioning
confidence: 99%